Characterization of potential drug-drug interactions in patients hospitalized in the intensive care unit of a tertiary hospital in Bogotá - Marcela Hernández; Gabriel Tribiño; Carlos Bustamante (Biomédica: revista del Instituto Nacional de Salud, 2018)
Introduction: Drug-drug interactions occur more frequently in intensive care units than in other services. However, in Colombia, there are few studies on this problem in critically ill patients. Objectives: To characterize potential drug-drug interactions generated from prescriptions during hospitalization in an intensive care unit and to determine factors associated with their onset. Materials and methods: A retrospective cohort was assembled with patients hospitalized in an intensive care unit for a seven-month period. The daily prescription was assessed for potential drugdrug interactions using the Lexicomp® program. We calculated the incidence of interactions, classified them by type, severity, and level of documentation, and evaluated the factors associated with their onset using logistic regression. Results: The proportion of patients with at least one interaction was 84% while 87% had more than one interaction; the median was six interactions per patient. The most frequent was fentanyl and midazolam (23%). Moderate interactions were the most frequent by severity (77.6%) and by documentation (52.6%). The most common index and precipitating drugs were midazolam (12%) and fentanyl (10.6%), respectively. Age (OR=3.1) and the number of drugs (OR=11.8) were associated with the occurrence of interactions. Conclusions: Given their high frequency and potential negative impact, the systematic monitoring of prescriptions in intensive care units to detect interactions is important. Such monitoring contributes to the rational use of medicines and to improve the quality of care.